Sanitasi Pantai dan Kualitas Perairan Pulau Mansinam pada Kondisi Arus Permukaan Monsun Timur - Jean Irene Wyzer; Sri Hartini; Max J. Tokede (Cassowary, 2019)
Domestic waste caused by human activities in the bay area periodically can accumulate the coast of Mansinam Island and have a negative impact on sanitation and water quality. The direction of sea level currents in the East Monsoon (June-August) is generally moved from the West and come into the bay area. This study aims as follow: 1) To analyze the water quality (physical, biological, chemical and dissolved metals) on the coast of Mansinam Island based on the required quality standards for marine tourism activities; 2) To Analyze the level of coastal pollution on Mansinam Island based on the value of the Pollution Index (PI); 3) To identify the type and volume of pollutants in the coastal area of ​​Mansinam Island in the East Monsoon. The PI indicates that at stations I, III and IV of the waters are lightly polluted, while the waters at the station II has been moderately polluted. The water quality parameter value of Station II has exceeded the quality standard for marine tourism in accordance with Kepmen. LH. No. 51 of 2004 consisting of TSS, nitrate, phosphate, oil and fat, total coliform and faecal coliform. In Station I, the water quality that exceeds the standard for nitrate, phosphate, and copper, while station III and station IV where higher on TSS value of nitrate, phosphate, oil and fat, and total coliform than the standard. Based on the results of the study, TSS values ​​at station I to station IV were 56.67 mg/L, 196 mg/L, 116 mg/L, and 157.33 mg/L respectively, while the fecal coliform value was 20 MPN / 100 ml,> 2400 MPN / 100 ml, 7.8 MPN/100 ml, and 11 MPN/100 ml. Nitrate and phosphate in Mansinam Island waters have an average value of 0.027 mg/L and 0.021 mg /L. The physical, biological, chemical and dissolved metals of Mansinam Island marine waters in East Monsoon from 19 parameters observed by 12 parameters (63%) are within the quality standard threshold and 7 parameters (37%) have been above the standard quality threshold for Marine tourism. Pollution levels based on the Pollution Index of Mansinam Island's marine waters are mildly polluted for marine tourism purposes. The composition and density of waste types are found to be different in conditions of ebb and tide because the seasons in Indonesia are under the influence of monsoons, where the wind determines the occurrence of waves and surface currents in the waters on the bay areas.